Dosis de humus de lombriz y su respuesta en la produccion de biomasa y rendimiento del cultivo de caupi( vigna unguiculata) en la banda de shilcayo- San martin-Peru - Valles Cabrera, Cinthya (2011)
This paper titled "Dose of vermicompost and its response in biomass production and crop yield of cowpea (Vigna unguiculata) in the Banda de Shilcayo - San Martin - Peru, aimed to evaluate the effect of vermicompost fertilization for fixing CO2 in the cultivation of cowpea (Vigna unguiculata) and determine the curve of CO2 fixation and peak biomass production in the cultivation of cowpea (Vigna unguiculata) and was conducted in the field using a randomized complete block design (RCBD) with 05 treatments, considering chemical control (NPK 75 - 60- 30 kg. ha- |), an absolute and 04 repetitions per treatment. The major findings were: On the grain yield, the T1 (4 tons of vermicompost) with an average of 2967.84 kg ha- 1 statistically exceeded the other treatments, T1 (4 tons of vermicompost ) with a value of 18,623 responded with regression of efficiency compared to fixed carbon content, the maximum rate of CO2 fixation was developed by the T1 between 45 and 55 days after planting and generally between 45 to 55 days for other treatments, but with lower values of change per unit of time.